2019
DOI: 10.1111/hepr.13416
|View full text |Cite
|
Sign up to set email alerts
|

Three criteria for radiological response on survival in patients with hepatocellular carcinoma treated with lenvatinib

Abstract: Lenvatinib (LEN) is a newly approved, multikinase inhibitor for treating unresectable hepatocellular carcinoma. In the present study, we investigated the impact of three different criteria for evaluating radiological objective response (OR) on overall survival in real-world data.Methods: Consent for LEN therapy was obtained from 51 patients from April 2018 to March 2019. A total of 40 patients who received a minimal cumulative duration of 4 weeks of LEN were included in the analysis. Enhanced computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 25 publications
1
31
1
Order By: Relevance
“…Physicians sometimes reduce lenvatinib doses due to lenvatinib-related AEs. 4,[14][15][16][17][22][23][24][25][26] In the present study, the most frequent cause that led to dose reduction or discontinuation of lenvatinib within 6 weeks was appetite loss (72.5%), and the median 2-6 W-RDI (69.6%) was significantly lower than the median 0-2 W-RDI (100%) due to the dose reduction or temporary interruption of lenvatinib. Hiraoka et al reported that appetite loss was an important AE in lenvatinib treatment for discontinuation clinically.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Physicians sometimes reduce lenvatinib doses due to lenvatinib-related AEs. 4,[14][15][16][17][22][23][24][25][26] In the present study, the most frequent cause that led to dose reduction or discontinuation of lenvatinib within 6 weeks was appetite loss (72.5%), and the median 2-6 W-RDI (69.6%) was significantly lower than the median 0-2 W-RDI (100%) due to the dose reduction or temporary interruption of lenvatinib. Hiraoka et al reported that appetite loss was an important AE in lenvatinib treatment for discontinuation clinically.…”
Section: Discussionmentioning
confidence: 44%
“…There have been several reports on the evaluation of antitumor response to lenvatinib using initial imaging, which were assessed from 4 to 8 weeks after lenvatinib introduction, in clinical practice. [14][15][16][17][22][23][24][25][26] These reports showed ORRs of 29.4-45.0% and DCRs of 60.0-93.0%. Similarly, the present study showed that relative to the image at baseline, the 6 W-ORR and 6 W-DCR were 50.0% and 90.0%, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…To date, lenvatinib showed a higher ORR of 41.3% compared with sorafenib in a randomized phase II non‐inferiority trial, and it also showed the ORR of 37.5–40.7% assessed by modified Response Evaluation Criteria in Solid Tumors in clinical settings . Meanwhile, a relative higher ORR of 61.3% was reported in patients with intermediate‐stage HCC according to the Japanese subgroup analysis of a randomized phase III study .…”
Section: Discussionmentioning
confidence: 95%
“…To date, lenvatinib showed a higher ORR of 41.3% compared with sorafenib in a randomized phase II noninferiority trial, 5 and it also showed the ORR of 37.5-40.7% assessed by modified Response Evaluation Criteria in Solid Tumors in clinical settings. [25][26][27][28] Meanwhile, a relative higher ORR of 61.3% was reported in patients with intermediate-stage HCC according to the Japanese subgroup analysis of a randomized phase III study. 29 However, Ueshima et al reported that patients with Child-Pugh score 5 and ALBI grade 1 showed better tolerability and it was easier to maintain the initial dose of lenvatinib than those with poor hepatic function, insisting that ALBI grade 1 was the favorable factor affecting the ORR in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Starting with a reduced dose was permitted based on the patient's condition and the preference of the attending physicians. Tumor assessment was done in accordance with the modified Response Evaluation Criteria in Solid Tumor (mRECIST), using dynamic CT within 4-8 weeks and every 8 weeks thereafter [16,17]. During follow up, all patients were measured routine blood-chemistry and tumor markers testing every 2-4 weeks.…”
Section: Protocol Of Len Therapymentioning
confidence: 99%